Effect of rinsing with water immediately after neutral gel and foam fluoride topical application on enamel remineralization: An in situ study - Delbem, Alberto Carlos Botazzo [UNESP]; Danelon, M.; Sassaki, K. T.; Vieira, A. E. M.; Takeshita, E. M.; Brighenti, Fernanda Lourenção [UNESP]; Rodrigues, E. (Pergamon-Elsevier B.V. Ltd, 2010)
Objective: The aim of this study was to evaluate, in situ, the effect of rinsing with water immediately after neutral fluoride foam application (Foam) or fluoride gel application (Gel).Design: Ten volunteers wore acrylic palatal appliances containing 4 enamel blocks selected by surface hardness with artificial caries. Five experimental regimes of 3 days each were set according to treatment: placebo; Gel and Foam followed by no rinsing or consuming of liquids or solids for the next 30 min; Gel and Foam followed by immediately washing with water jet. After each phase, surface hardness was again measured for analysis of mineral gain, evaluated through percentage of surface hardness recovery (%SHR) and integrated loss of subsurface hardness (Delta KHN). The concentration of loosely bound fluoride (CaF2) and firmly bound fluoride (FA-like) formed and retained were also determined.Results: Fluoride treatments produced greater remineralization (%SHR and Delta KHN) compared to placebo group (p < 0.05). There was no difference in the ability to promote remineralization and in the concentration of fluoride formed and retained, in each analysis, between Gel and Foam (p > 0.05).Conclusion: The data suggest that rinsing with water immediately after topical application does not seem to have an influence on the ability of fluoride to promote remineralization. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Enamel; Topical fluoride; Caries prevention